New Genre Arctic Art and Art Education Exhibition : Shifting River: You can’t Step Twice into the Same River, 2024 - Jokela, Timo (Stormen Concert Hall, 2024)
The artwork combines feldwork in Canada, in the Yukon goldfelds along the Klondike River, and in Finnish Lapland on the banks of the Ounas River and its tributary, the Loukinen River. The lives of the Indigenous Han people who lived at the mouth of the Klondike River were changed radically during the time of the Klondike Gold Rush more than one hundred year ago. My home river, the Ounas, in North Finland, was protected by law in the early 1980s, but the Kittilä Gold Mine has now built a discharge pipe for mine’s wastewater into Loukinen, one of Ounas’s major tributaries. In my work, I examine the signifcance of the river, its meaning for local culture, current changes, and the future threats it faces. By the artwork I try to make visible the stories written on the surface of the water and deep under. I agreed with Heraclitus words: You can’t step twice in the same river Video and installation, 8 min., variable dimension, 2024.